LEGALITAS SISTEM PEER TO PEER LENDING FINANCIAL TECHNOLOGY DI INDONESIA - Ditarizky Wijayanti; ' Pujiyono (Jurnal Privat Law, 2021)
Abstrack:This research aims to examine the legal protection of investor in peer to peer lending platform in Indonesia. The problem formulation of this research consists two things: what is the regulation of peer to peer lending platform in Indonesia and what kind of risk that investor faced thorugh investement in peer to peer lending . This normative research uses a statutory and conceptual approach with the nature of prescriptive research. The result showed that there was regulations that adjust about the legal protection in prefentive and repressive  for investor in peer to peer lending. But there aren’t any specific regulation that adjust about financial technology and peer to peer lending itself.AbstrakPenelitian ini bertujuan mengkaji terkait perlindungan hukum bagi investor peer to peer lending di Indonesia. Permasalahan yang dibahas adalah terkait bagaimana regulasi hukum mengenai peer to peer lending serta kelemahan penerapan peer to peer lending di Indonesia. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan sifat penelitian preskriptif dengan menggunakan pendekatan statute approach dan conseptual approach. Hasil penelitian menunjukkan bahwa memang sudah ada pengaturan yang mengatur terkait perlindungan hukum bagi investor secara preventif dan represif, tindakan represif bisa dilaksanakan melalui jalur non litigasi dan litigasi, namun belum ada undang-undang secara spesifik yang mengatur terkait financial technology dan peer to peer lending itu sendiri.